Proceedings of the 2014 Annual Conference on Genetic and Evolutionary Computation 2014
DOI: 10.1145/2576768.2598246
|View full text |Cite
|
Sign up to set email alerts
|

Evolved spacecraft trajectories for low earth orbit

Abstract: In this paper we use Differential Evolution (DE), with best evolved results refined using a Nelder-Mead optimization, to solve complex problems in orbital mechanics relevant to low Earth orbits (LEO). A class of so-called 'Lambert Problems' is examined. We evolve impulsive initial velocity vectors giving rise to intercept trajectories that take a spacecraft from given initial positions to specified target positions. We seek to minimize final positional error subject to time-of-flight and/or energy (fuel) const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, in preliminary testing on other trajectory optimization problems [9], it was found that, while CMA-ES converged more quickly, it had a greater tendency to become trapped in local minima. In contrast, DE more consistently converged to the correct solutions.…”
Section: The Differential Evolution Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in preliminary testing on other trajectory optimization problems [9], it was found that, while CMA-ES converged more quickly, it had a greater tendency to become trapped in local minima. In contrast, DE more consistently converged to the correct solutions.…”
Section: The Differential Evolution Algorithmmentioning
confidence: 99%
“…Evolutionary methods utilized have included genetic algorithms [2,3], particle swarm optimization [4], monotonic basin hopping [5], simulated annealing [6], and differential evolution [7]. To a lesser extent, EC methods have also been leveraged for in-orbit trajectory planning about planets [8][9][10].…”
Section: Introductionmentioning
confidence: 99%